Independent Association of Erectile Dysfunction and Low Testosterone Levels with Life Dissatisfaction in Men with Chronic Spinal Cord Injury. Issue 5 (20th February 2020) - D'Andrea, Settimio; Minaldi, Elisa; Castellini, Chiara; Cavallo, Francesca; Felzani, Giorgio; Francavilla, Sandro; Francavilla, Felice; Barbonetti, Arcangelo
Abstract: Background: The loss of global functional independence, along with bladder, bowel, and sexual dysfunctions, may contribute to psychological distress and life dissatisfaction after spinal cord injury (SCI). Aim: To explore the relationship of erectile function and androgenic status with life satisfaction, independently from confounders recognizable in spinal cord–injured men. Methods: 100 consecutive men (49 ± 17 years) admitted to a rehabilitation program because of chronic SCI (≥1 year) underwent clinical/biochemical evaluations, including the assessment of life and sexual satisfaction using the Life-Satisfaction Questionnaire-9 (LiSat-9), erectile function using the International Index of Erectile Function-5 (IIEF-5), global and bowel-bladder functional independence using the Spinal Cord Independence Measure (SCIM) and measurement of total testosterone (TT) levels. The free testosterone level was calculated using the Vermeulen formula. Outcomes: The outcomes include the relationship between sexual health and life satisfaction in men with SCI. Results: A LiSat-9 score <4, suggestive for life dissatisfaction, was exhibited by 49% of men. When compared with the life-satisfied group, a significantly higher percentage of them had sexual dissatisfaction and erectile dysfunction (ED); they also exhibited significantly lower levels of TT and calculated free testosterone (cFT) and a more severe impairment of bowel-bladder function. The life satisfaction degree correlated with sexual satisfaction degree, IIEF-5 score, TT, cFT, and bowel-bladder function degree. At the logistic regression model, including sexual LiSat-9 subscore and bowel-bladder SCIM subscore, only the former exhibited a significant negative association with life dissatisfaction. In a further logistic regression model, including the putative key determinants of sexual satisfaction, erectile function, and cFT levels, a higher odd of life dissatisfaction was independently associated both with a lower IIEF-5 score (OR: 0.93; 95% CI: 0.88, 0.98) and lower cFT levels (OR: 0.98; 95% CI: 0.98, 0.99). Clinical Implications: In men with chronic SCI, assessment of erectile function and testosterone levels can help to predict life satisfaction. Strengths & Limitations: This is the first demonstration of the independent association of androgen deficiency and ED with life satisfaction in men with SCI. Prospective studies are warranted to clarify the cause-effect relationships. Conclusions: In men with SCI, ED and low testosterone levels exhibit a significant independent association with life dissatisfaction; longitudinal intervention studies could explore possible effects of their treatment in improving sexual and life satisfaction in this population.